INVESTIGATION ON THE DYNAMICS OF MOVEMENT OF CYLINDRICAL CLEANING PIGS THROUGH THE BENDS OF PIPELINE SYSTEMS FOR FLUID TRANSPORTATION - Serhii STETSIUK; Yaroslav DOROSHENKO; Robert BONDARENKO; Oleksandr FІLIPCHUK; Volodymyr VOLOVETSKYI (Scientific Journal of Silesian University of Technology. Series Transport)
Development and implementation of methods for cleaning the internal cavity of pipelines in the process of transporting fluids is important to ensure their energy efficiency and safe operation. The dynamics of the movement of one-piece cylindrical cleaning pistons made of various materials (silicone compound, self-destructive elastic polymer composition, polyurethane foam assembly foam) in the pipelines of pipeline systems intended for fluid transportation were studied by modelling and experimentally. The dynamics of movement of solid cylindrical cleaning pigs made from various materials (silicone compound, self-destructive elastic-polymer composition, polyurethane foam) in bends of pipeline systems intended for fluid transportation were studied through modelling and experiments. The analysis of forces acting on the pig during its movement in the pipeline bend was conducted, and the equations of pig motion based on Newton's second law were formulated. Contact forces of normal reaction, arising due to pig bending in the pipeline bend and determining the magnitude of frictional force between the pig and the inner wall of the bend, were determined based on classical bending theory. The impact of the material's modulus of elasticity, from which the pig is made, on the magnitude of contact forces of normal reaction at the pig pressing points against the inner wall of the pipeline bend was established. A method for determining the conditions under which pigs made from different materials will pass through pipeline bends without stopping and getting stuck was proposed. An equation for calculating the minimum allowable pig movement speed at the entrance to the bend to ensure its passage without stopping and getting stuck was derived.